The essential oils in agriculture as an alternative strategy to herbicides: a case study. (5th May 2009) - Zanellato, Miriam; Masciarelli, Eva; Casorri, Laura; Boccia, Priscilla; Sturchio, Elena; Pezzella, Mario; Cavalieri, Andrea; Caporali, Fabio
In this study we investigated the allelopathic effect of some essential oils extracted from aromatic plants to inhibit weed seed germination. The study was performed to evaluate the potential genotoxic effect of lavender on Vicia faba root meristems by genotoxicity tests (comet assay and micronuclei test) and to evaluate microbial diversity fluctuation by Restriction Fragment Length Polymorphism (RFLP) molecular analysis on ecological, biological and conventional soil. The results showed a phytotoxicity effect of the essential oil for all the concentration tested, while there is not a dose-dependent relation between oil concentrations and the genotoxic effect. A fluctuation of microbial communities in relation to the release of essential oils by Lavandula officinalis was also observed. Then we suggest that the essential oils could be useful as potential bioherbicides as an alternative strategy to the chemical remedy, but further studies are necessary to evaluate their appropriate use in the field.